To Be Born Is Not Enough: The Key Role of Innovative Startups - Alessandra Colombelli; Jackie Krafft; Marco Vivarelli (Institute for the Study of Labor (IZA), 2016)
This paper investigates the reasons why entry per se is not necessarily good and the evidence showing that innovative startups survive longer than their non-innovative counterparts. In this framework, our own empirical analysis shows that greater survival is achieved when startups engage successfully in both product innovation and process innovation, with a key role of the latter. Moreover, this study goes beyond a purely microeconomic perspective and discusses the key role of the environment within which innovative entries occur. What is shown and discussed in this contribution strongly supports the proposal that the creation and survival of innovative start-ups should become one qualifying point of the economic policy agenda.
Keywords: L26; O33; 330; innovation; startups; survival; product innovation; process innovation